2019
DOI: 10.1016/j.cjtee.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre collaborative cohort study of the use of Kirschner wires for the management of supracondylar fractures in children

Abstract: PurposeSupracondylar fractures of the humerus cause significant morbidity in children. Nerve damage and loss of fracture reduction are common recognised complications in patients with this injury. Uncertainty surrounds the optimal Kirschner wire configuration and diameter for closed reduction and pinning of these fractures. This study describes current practice and examined the association between wire configuration or diameter and outcomes (clinical and radiological) in the operative management of paediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…Practically, the addition of the Gartland IV-type fracture did not alter the currently recommended method of treatment of the originally described Gartland III-type fractures by means of CRPP. CRPP remains, for most surgeons, the standard treatment for displaced extension type supracondylar fractures of the elbow, whether these fractures are of the Gartland III type or the Gartland IV type [13]. Furthermore, the distinction between the Gartland III and Gartland IV-type fractures is a strict intraoperative finding and cannot be concluded on patient admission.…”
Section: Discussionmentioning
confidence: 99%
“…Practically, the addition of the Gartland IV-type fracture did not alter the currently recommended method of treatment of the originally described Gartland III-type fractures by means of CRPP. CRPP remains, for most surgeons, the standard treatment for displaced extension type supracondylar fractures of the elbow, whether these fractures are of the Gartland III type or the Gartland IV type [13]. Furthermore, the distinction between the Gartland III and Gartland IV-type fractures is a strict intraoperative finding and cannot be concluded on patient admission.…”
Section: Discussionmentioning
confidence: 99%
“…More than two wires are sometimes used particularly when fractures are unstable either with three lateral wires or three to four wires in cross wire configuration. It has been shown that fracture reduction is maintained better with three wires in crossed configuration (two lateral and one medial wire) and had a smaller change in Baumann angle compared to those fractures treated with other pin configurations [34].…”
Section: K-wire Configurationmentioning
confidence: 99%
“…As fraturas supracondilares umerais representam um terço de todas as fraturas pediátricas de membros em crianças com menos de 7 anos de idade, e são uma causa de morbidade significativa na população pediátrica. 1,2 As complicações mais encontradas neste cenário incluem lesões neurovasculares, síndrome compartimental, má consolidação e comprometimento funcional. 1,2 Lesões nervosas e vasculares podem ser iatrogênicas ou podem ocorrer após um evento traumático.…”
Section: Introductionunclassified
“…1,2 As complicações mais encontradas neste cenário incluem lesões neurovasculares, síndrome compartimental, má consolidação e comprometimento funcional. 1,2 Lesões nervosas e vasculares podem ser iatrogênicas ou podem ocorrer após um evento traumático. O comprometimento vascular pode ser causado por ruptura do vaso, torção, compressão, espasmo ou lesão intimal, e a incidência aumenta com o grau de luxação da fratura.…”
Section: Introductionunclassified
See 1 more Smart Citation